Human Immunodeficiency Virus as a Sexually Transmitted Disease: Manitoba’s HIV Unlinked Seroprevalence Study - Laila Sekla; Gregory Hammond; Robert Tate; Walter Stackiw; Gudrun Eibisch; Sherlyn Shewchook (Canadian Journal of Infectious Diseases)
Objective: To determine the prevalence of human immunodeficiency virus (HIV)-1 infections.